The Most Important Risk Factors and Associated Morbidities of Bronchopulmonary Dysplasia, the Never Ending Problem of Preterms - Ayşen Bayrak; İpek Güney Varal; Pelin Doğan; Elif Güler Kazancı (Güncel Pediatri)
Introduction: Currently, many morbidities in preterms born at low birth weight and gestational week have decreased with improvements in premature infant care. However, as the survival chances of preterms born earlier have increased, a decrease in the frequency of bronchopulmonary dysplasia (BPD) has not been achieved. In this study, the risk factors of BPD, associated morbidities and its effect on mortality will be evaluated. Thus, it is aimed to decrease the incidence of BPD with new treatment and prevention strategies. Materials and Methods: In this retrospective cohort study, preterms born in our hospital between January 2018 and December 2021 in the level 3 NICU less than 32 weeks of gestational age and/or 1500 g were included. The presence of BPD was determined in 2 groups as mild and moderate-severe BPD and associated risk factors and morbidities were evaluated. Results: After the exclusion criteria were met, 363 preterm infants were included in the study. Of these babies, 33.1% (n=120) were diagnosed with BPD and 57.8% (n=69) of them were diagnosed with moderate-severe BPD. The frequency of BPD increased as birth weight and gestational week decreased. The risk of BPD increased significantly as the Apgar score decreased and the need for resuscitation increased (p<0.05). Respiratory distress syndrome(RDS) and patent ductus arteriosus(PDA) requiring treatment were observed more frequently in infants with a diagnosis of BPD(p<0.001). In patients with BPD, the incidence of ventilator-associated pneumonia(VAP), osteopenia of prematurity and retinopathy of prematurity(ROP) were found to be significantly higher (p<0.001). As a result of multivariate logistic regression analysis, it was found statistically significant that the likelihood of BPD increased 3.6-fold in infants with RDS, increased 6.2-fold in infants with VIP, and increased 4.6-fold in infants with osteopenia of prematurity. Conclusion: The incidence of BPD and moderate to severe BPD is found to be increased in preterms. In the study, it was shown that the risk of BPD increased significantly in preterms with a history of VIP and accompanying osteopenia of prematurity. Bronchopulmonary dysplasia and moderate to severe BPD have been shown to be associated with mortality and it is thought that it is important to determine the risk groups for prevention.